The jump from
10 = ax - 3b
to
10 = x(a - 3b)
is incorrect
Why? Because there is NO x term attached to the 3b. Notice how if you distrbute the x back in, you'll go from x(a-3b) to ax - 3bx, but again there is no x in the original 3b term.
Because step 2 is incorrect, it naturally leads that step 3 is incorrect
--------------------------------------------------------
Here is how to solve for x
10 = ax - 3b
10+3b = ax - 3b+3b .... add 3b to both sides
10+3b = ax
ax = 3b+10
ax/a = (3b+10)/a .... divide both sides by 'a'
x = (3b+10)/a